2022
DOI: 10.1038/s41593-022-01084-8
|View full text |Cite
|
Sign up to set email alerts
|

Faulty autolysosome acidification in Alzheimer’s disease mouse models induces autophagic build-up of Aβ in neurons, yielding senile plaques

Abstract: Autophagy is markedly impaired in Alzheimer’s disease (AD). Here we reveal unique autophagy dysregulation within neurons in five AD mouse models in vivo and identify its basis using a neuron-specific transgenic mRFP-eGFP-LC3 probe of autophagy and pH, multiplex confocal imaging and correlative light electron microscopy. Autolysosome acidification declines in neurons well before extracellular amyloid deposition, associated with markedly lowered vATPase activity and build-up of Aβ/APP-βCTF selectively within enl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
326
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 387 publications
(349 citation statements)
references
References 61 publications
23
326
0
Order By: Relevance
“…A recent study suggests that cored deposits may originate from Aβ aggregates that initially form within endosomal/lysosomal compartments [ 42 ]. It is not known whether diffuse deposits could also originate in intracellular compartments.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study suggests that cored deposits may originate from Aβ aggregates that initially form within endosomal/lysosomal compartments [ 42 ]. It is not known whether diffuse deposits could also originate in intracellular compartments.…”
Section: Discussionmentioning
confidence: 99%
“…Aβ peptides are generated from the sequential cleavage of APP by β- and γ-secretases within vesicles inside cells and on the plasma membrane, and are normally secreted under physiological conditions [ 42 ]. On the other hand, there is evidence showing the presence of intracellular Aβ, particularly in mouse models of amyloidosis [ 24 , 25 , 26 , 27 , 28 , 29 ], suggesting that some Aβ is retained inside the neurons. However, the detailed properties of intracellular Aβ are not fully established.…”
Section: Discussionmentioning
confidence: 99%
“…In transgenic rodents designed to develop amyloidosis, large amounts of early intraneuronal Aβ were observed prior to the formation of plaques, which could be linked to deficits in synaptic plasticity, learning, and memory [ 27 , 28 ]. A recent study has added a new significant insight that the deficit in the autolysosome acidification, accompanied by the accumulation of C99 and Aβ peptides, is an early event in neurons, and such neurons could be the principal sources of neuritic plaques in amyloidosis models [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have attributed the neuronal damage observed in AD to what happens following the accumulation of β-amyloid (Aβ) outside the cell, rather than before it and inside the neuron. Recent studies have found that the neuronal damage observed in AD may be attributed to the lower activity of lysosomal acidic enzymes in brain cells; before plaques are formed outside the cells, the nerve cells are paralyzed [ 21 ].…”
Section: Possible Triggers and Mechanisms Of Cognitive Decline In The...mentioning
confidence: 99%